S66 Delivering the 100, 000 genomes project to establish the functional role of DNA sequence variants in respiratory rare diseases. (12th November 2019) - Shovlin, CL; Morris-Rosendahl, DJ; Copeland, F; De Soyza, A; Hogg, C; Jenkins, G; Marciniak, SJ; Lovett, M; Moffatt, MF; Cookson, WOC; Alikian, M; Hasan, S; et al.
Abstract : Background and aims: Between July 2016 and September 2018, NHS Genomic Medicine Centres (GMCs) recruited families with specified rare diseases to the 100, 000 Genomes Project for whole genome sequencing (WGS), and linkage to phenotypic information from NHS Health Records. Methods: Genomics England protocols were followed for disease nominations, data model generation based on human phenotype ontology (HPO) terms, 1 and development/review of PanelApp gene panels. 2 Genomics England performed all WGS, data alignments, and initial variant tiering. This incorporated appropriate familial segregation patterns for variants in genes known to cause the patient's disease (Tier 1: clear loss of function variants, Tier 2 : other variants), and clear loss of function or de novo variants in other genes (Tier 3). The Respiratory GeCIP (Clinical Interpretation Partnership) was established to analyse full WGS/phenotypic datasets. Results: Six respiratory diseases were nominated and passed through 100K pipelines: primary ciliary dyskinesia (PCD), familial pulmonary fibrosis (FPF), aggressive non-CF bronchiectasis, pulmonary arteriovenous malformations (PAVMs), hereditary haemorrhagic telangiectasia (HHT) and familial pneumothorax. National and international networks were established for each, including a focus on patient/public engagement. Patient results were returned to UK GMCs from August 2017. Recruited participants with recessive and dominant diseases each had 0–2 Tier 1 variants, 0–2 Tier 2 variants and up to 536 Tier 3 variants. Genomic diagnoses have been fed back to 57 respiratory families for 15 different genes in PCD, FPF, non-CF bronchiectasis, and PAVMs/HHT, already modifying PanelApp, with validations in two potentially new ciliopathy genes in progress. Full WGS results have been released quarterly to the Research Data Embassy at steadily increasing numbers. HPO term capture identifies further patients; for example, there are data on 269 families recruited with bronchiectasis plus another 27 with relevant HPO terms. Respiratory GeCIP Data Embassy access and Projects were secured through 2018–2019. New analytic resources available through the Data Embassy (particularly LabKey and IVA 2.0) enable >90 Domain members to identify annotated variants through indexed systems. Custom scripts are being used to access variant information from the whole genome. Conclusions: The Respiratory GeCIP has established a collaborative resource for the advancement of NHS Respiratory Genomics. References: http://human-phenotype-ontology.github.io/ https://bioinfo.extge.co.uk/crowdsourcing/PanelApp